2019
DOI: 10.1186/s13256-019-2222-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute human bocavirus 1 infection in child with life-threatening bilateral bronchiolitis and right-sided pneumonia: a case report

Abstract: Background Human bocavirus 1 is a commonly detected human parvovirus. Many studies have shown human bocavirus 1 as a pathogen in association with acute respiratory tract infections in children. However, because human bocavirus 1 persists in the upper airways for extensive time periods after acute infection, the definition and diagnostics of acute human bocavirus 1 infection is challenging. Until now, detection of human bocavirus 1 exclusively, high viral load in respiratory samples, and viremia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…[ 21 ] 2008 French 192 NA NA Nasopharyngeal Aspirate 8.6 24 12.5 10 14 Midulla F et al. [ 11 ] 2010 Italy 182 NA NA Nasal Washings 2.5 22 12.5 15 7 Ricart S et al. [ 16 ] 2013 Spain 484 235 173 Nasopharyngeal Aspirate 12 119 24.58 NA NA Wang k et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] 2008 French 192 NA NA Nasopharyngeal Aspirate 8.6 24 12.5 10 14 Midulla F et al. [ 11 ] 2010 Italy 182 NA NA Nasal Washings 2.5 22 12.5 15 7 Ricart S et al. [ 16 ] 2013 Spain 484 235 173 Nasopharyngeal Aspirate 12 119 24.58 NA NA Wang k et al.…”
Section: Resultsmentioning
confidence: 99%
“…So far, there has been one fatality reported in an immunocompetent child due to severe acute bronchiolitis caused by HBoV [ 11 ]. Some studies have described the HBoV as the second or third most prevalent cause of bronchiolitis [ 3 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The more widespread detection of FBoV-1 in cats with enteric disease (Yi et al 2018 ) may indicate that different genotypes may exhibit different phenotypic characteristics, just like some members of bocaparvoviruses. For example, human bocaparvovirus 1 (HuBoV-1) is often associated with respiratory disease (Koseki et al 2012 ; Meriluoto et al 2012 ; Ziemele et al 2019 ) while HuBoV-2–4 has been associated with enteric diseases (Cheng et al 2011 ; Jin et al 2011 ). Garigliany et al ( 2016 ) reported the presence of FBoV-1 in the brain of an FPV-infected cat with neurological findings.…”
Section: Discussionmentioning
confidence: 99%
“…HBoV1 is often detected in conjunction with other pathogens; the frequency of coinfections is high, and the clinical symptoms are more severe than those associated with monoinfections (Sun et al, 2019 ). However, there have been instances of life-threatening infections caused by a single infection (Ziemele et al, 2019 ). Furthermore, it is not yet known whether HBoV is a true ARI pathogen, making the diagnosis of acute HBoV1 infection very challenging.…”
Section: Introductionmentioning
confidence: 99%